2000
DOI: 10.1210/mend.14.6.0473
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1 (HIF-1) Up-Regulates Adrenomedullin Expression in Human Tumor Cell Lines during Oxygen Deprivation: A Possible Promotion Mechanism of Carcinogenesis

Abstract: Little is known about the molecular mechanisms that control adrenomedullin (AM) production in human cancers. We demonstrate here that the expression of AM mRNA in a variety of human tumor cell lines is highly induced in a time-dependent manner by reduced oxygen tension (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
132
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(144 citation statements)
references
References 57 publications
12
132
0
Order By: Relevance
“…Both ADM and bFGF are known to be upregulated by hypoxia (Cormier-Regard et al, 1998;Nakayama et al, 1998;Le and Corry, 1999;Nguyen and Claycomb, 1999;Garayoa et al, 2000). TAM has been shown to induce hypoxia in MCF-7 xenografts (Evans et al, 1997).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…Both ADM and bFGF are known to be upregulated by hypoxia (Cormier-Regard et al, 1998;Nakayama et al, 1998;Le and Corry, 1999;Nguyen and Claycomb, 1999;Garayoa et al, 2000). TAM has been shown to induce hypoxia in MCF-7 xenografts (Evans et al, 1997).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…1). To examine the effects of Txn1 overexpression on HIF-1α activity, we determined the mRNA levels, in normoxic and hypoxic conditions, of two genes, VEGF and ADM, which are angiogenic growth factors induced by HIF-1α (Cormier-Regard et al, 1998;Forsythe et al, 1996;Garayoa et al, 2000). We found that the hypoxic-induction of VEGF and ADM mRNA was significantly increased in HeLa, HT-29 and EMT6 cells overexpressing Txn1, but not in MCF-7 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…41 AM has been shown to stimulate tumor angiogenesis through induction of HIF-1. 20 In addition, AM acts as a proangiogenic factor in vivo in breast cancer 42 and endometrial tumors. 43 Therefore, it will be of interest to examine interaction between AM, IL-8 and IL-13R␣2 in relation to tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…18 AM expression and secretion is stimulated by hypoxia, lipopolysaccharide and NO. 17,19,20 In the context of cancer, AM seems to play a growth-modulatory effect in prostate carcinoma. To investigate the role of AM in prostate carcinoma, we previously generated PC-3 cell line clones, which express high levels of AM.…”
mentioning
confidence: 99%